Pengaruh Pengetahuan Perpajakan, Sanksi Pajak dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Batam Selatan Dengan Sistem Perpajakan Online Sebagai Variabel Intervening - Rucyana; Satriawan, Bambang; Puspita Dewi, Nolla (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of tax knowledge, tax saction and tax rate on compliance taxpayer of private person with online tax system as a mediating variable at KPP Pratama Batam Selatan. The population used is an individual taxpayer registered at KPP Pratama Batam Selatan. This research is a type of quantitative research. The sampling method used in this study is accidental sampling and purposive sampling with a sample of 100 individual taxpayers who are registered at KPP Pratama Batam Selatan. This study uses primary data obtained from questionnaires. The analytical method used in this study is PLS-SEM using the SmartPLS version 4.1.0 application. The results show that the tax knowledge has a positive and significant effect on individual taxpayer compliance, tax saction has a positive and significant effect on individual taxpayer compliance, tax rate has a positive and significant effect on individual taxpayer compliance, online tax system has a positive and significant effect on individual taxpayer compliance. The tax knowledge, tax sanction and tax rate have a positive and significant effect on the online tax system. The online tax system can mediate the effect of tax knowledge, tax sanction and tax rate on compliance taxpayer of private person at KPP Pratama Batam Selatan.